Galen's epistemology experience, reason, and method in ancient medicine - Hankinson, Robert J. 1957-; Havrda, Matyáš 1972- (Cambridge University Press, 2022)
Determining what has gone wrong in a malfunctioning body and proposing an effective treatment requires expertise. Since antiquity, philosophers and doctors have wondered what sort of knowledge this expertise involves, and whether and how it can warrant its conclusions. Few people were as qualified to deal with these questions as Galen of Pergamum (129-ca. 216). A practising doctor with a keen interest in logic and natural science, he devoted much of his enormous literary output to the task of putting medicine on firm methodological grounds. At the same time he reflected on philosophical issues entailed by this project, such as the nature of experience, its relation to reason, the criteria of truth, and the methods of justification. This volume explores Galen's contributions to (mainly scientific) epistemology, as they arise in the specific inquiries and polemics of his works, as well as their legacy in the Islamic world